THE RETROSPECTIVE ANALYSIS OF THE PERSONNEL POTENTIAL OF THE DIPLOMATIC SERVICE FOR THE PERIOD 2017-2020 - Палагусинець, Ростислав (SWorldJournal, 2020)
The paper studies the diplomatic service of Ukraine as one of the important structural elements in the system of public administration of Ukraine in the modern international relations. The system of the diplomatic service of Ukraine at the present stage i